Pathways to care with HIV-associated cryptococcal meningitis in Botswana and Uganda: Findings from a qualitative methods study - David S. Lawrence; Agnes Ssali; Neo Moshashane; Georgina Nabaggala; Lebogang Maphane; Thomas S. Harrison; David Meya; Joseph N. Jarvis; Janet Seeley (SSM: Qualitative Research in Health, 2023)
HIV-associated cryptococcal meningitis remains a key driver of AIDS-related mortality. Mortality is twice as high in those who present later to care and with severe symptoms such as confusion. We embedded a qualitative methods study within a randomised controlled trial in Gaborone, Botswana and Kampala, Uganda with the aim of understanding pathways to care. We conducted in-depth interviews with trial participants and surrogate decision makers and analysed data thematically. Between January 2020 and June 2021 we interviewed 58 individuals. Pathways to care were prolonged because headaches were disregarded by participants and healthcare workers as a common occurrence with a broad differential diagnosis of predominantly benign aetiologies. There was also a lack of awareness of cryptococcal meningitis, and it was often after HIV was diagnosed or disclosed that the pathway accelerated, resulting in hospital admission. We outline key recommendations to reduce mortality and argue for the integration of social and behavioural interventions within differentiated service delivery models for advanced HIV disease.